An Ecological Study of the Bhil Tribe in Rajasthan - Dr. Renu Sharma (Innovative Research Thoughts, 2023)
This study was done with forty days experience of staying and learning with the community. Bhils are listed as indigenous people of the states of Gujarat, Madhya Pradesh, Chhattisgarh, Maharashtra and Rajasthan—all in the western Deccan regions and central India—as well as in Tripura in far-eastern India, on the border with Bangladesh. Bhils are divided into a number of endogamous territorial divisions, which in turn have a number of clans and lineages. Most Bhils now speak the language of the region they reside in, such as Marathi, Gujarati or a Hindustani dialect. This study includes different dimensions of this tribe. It clearly describes the social, cultural, economic, and the ecological dimension of the tribe. The information are mainly collect through participatory approach, where an active participation of both community and researcher make this study very rich